La formación de abogados y abogadas : nuevas configuraciones, de Manuela Graciela González y María Gabriela Marano (comps.) - Montenegro, Jessica (2015)
"Manuela Graciela González and María Gabriela Marano (eds.). -- The new configurations of the field of legal training in Argentina. -- La Plata: Imás, 2014."